(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article considers the justification of its own theoretical approaches to accounting and balance policy on the basis of legal, scientific, and theoretical positions of their organization and proposes author definitions of the terms "accounting policy" and "balance policy". The authors prove that the concept of "accounting" and "balance" policy coincides in part, at least in the word "politics". Although the content of these concepts covers common elements, we argue that each of these concepts also includes components that are not elements of another concept. It is stressed that these concepts can not be identified in any way.